Roy Rappaport: Ritual and Religions in the Making of Humanity - Jensen, Hans J. Lundager (Religionsvidenskabeligt Tidsskrift, 2003)
Review-artikel af Roy A. Rappaport, Ritual and Religion in the Making of Humanity, Cambridge University press 1999